EMPOWERING SELF-HELP GROUPS (SHGS): PARADIGM SHIFT IN DAY-NULM - Monika; Marwah, Aparna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The SelfHelp Groups usually provide support services to corporate owners and individuals in similar social and financial situations to assist urban poor individuals in preparing for employment and self-employment. The government’s DAY-NULM (Deen Dayal Upadhaya- National Urban Livelihoods Mission) programme utilizes Self-Help Groups, Area Level Federations (AFL), and City-Level Federations (CFL) to offer financial solutions besides skill development to slum of urban disadvantaged households. While the SHGs provide a platform for ALF and CFL along with their knowledge enhancement usually provide social and economic empowerment through partnerships with local government and financial institutions. The SHGs enhanced living standards through borrowing and saving with the needy one. Urban Local Bodies (ULB) are permitted to combat urban poverty by offering housing, employment opportunities, and skill-building initiatives, with the help of the business sector, in an effort in order to raise living standards and financial situation of city residents. In a recent report issued by one of the Big 4 group (Deloitte) for Women at Work-2024, highlighted workplace issues like stress, stigma, and lack of support for health and caregiving responsibilities along with also highlighted inadequate gender equality efforts, safety concerns, harassment, and non-inclusive behaviors. The study emphasis over awareness financial security and physical wellbeing and revenue generation DAY NULM playing significant role specially assisting the youth in urban area and SHGs are seriously aimed towards ensuring basic amenities and fostering economic growth especially metropolitans regions.